Answers

2016-04-13T16:48:23+05:30
Let the probability of success be 'x'
and the probability of failure be 'y'
By the problem,x-y=3/13---------(1)
But we already know that x+y=1-------(2)
adding (1) and (2),
x-y+x+y=3/13+1
2x=(3+13)/13
2x=16/13
x=16/26
x = 8/13
Now substituting 'x' in (2),
8/13 + y = 1
y=1-8/13
y=(13-8)/13
y=5/13.
Therefore,probability of success 'x' is 8/13
and the probability of failure 'y' is 5/13.


0
2016-04-13T20:26:39+05:30
Let ,
The probability of success = x
The probability of failure = y
probability of success - probability of failure = 3/13
x - y = 3/13
We know that
probability of success + probability of failure = 1
x+y = 1

2x = 1+3/13
2x = 16/13
x = 8/13

y = 1- 8/13
y = 5/13
0